2014
DOI: 10.1057/hep.2014.9
|View full text |Cite
|
Sign up to set email alerts
|

The Drive to Internationalize: Perceptions and Motivations of Israeli College Directors

Abstract: Given the relatively high degree of academic freedom granted to institutions in Israel in conjunction with the lack of governmental policy on internationalization, directors of higher education institutions comprise key agents in the institutional internationalization process that is taking place in Israeli higher education. In this study, we took a qualitative approach to explore the views and attitudes of seven college directors in Israel. We show that motivation for internationalization is a multifaceted ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
18
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 29 publications
1
18
0
2
Order By: Relevance
“…Notably, Israeli college directors interviewed in a previous study by two of the authors (Yemini et al 2014a) interpret internationalization in differing manners, depending on the characteristics of the institutions they lead (as per Knight 2004). Indeed, Yemini et al (2014a) found that although all second-tier Israeli colleges function under strict financial constraints and strive to upgrade their status and to compete with established research universities, it seems that colleges' orientation, population and location are the most influential factors regarding their motivation to internationalize.…”
Section: Internationalization At Second-tier Israeli Higher Educationmentioning
confidence: 99%
See 4 more Smart Citations
“…Notably, Israeli college directors interviewed in a previous study by two of the authors (Yemini et al 2014a) interpret internationalization in differing manners, depending on the characteristics of the institutions they lead (as per Knight 2004). Indeed, Yemini et al (2014a) found that although all second-tier Israeli colleges function under strict financial constraints and strive to upgrade their status and to compete with established research universities, it seems that colleges' orientation, population and location are the most influential factors regarding their motivation to internationalize.…”
Section: Internationalization At Second-tier Israeli Higher Educationmentioning
confidence: 99%
“…These reasons include the relatively less developed research programs at such institutions (indeed, research often provides an international platform for collaborative teaching and learning); inadequate financial and other resources; and sometimes also a lack of prestige and academic reputation, which hinders and challenges the development of international connections (Yemini et al 2014a). Nevertheless, the barriers to internationalization are not sector-specific.…”
Section: Internationalization In Second Tier Institutionsmentioning
confidence: 99%
See 3 more Smart Citations